PROFIL KEMAMPUAN SISWA SMA DALAM MENYELESAIKAN SOAL UJI KOMPETENSI LABORATORIUM (UKL) PADA KEGIATAN PEKAN RAYA BIOLOGI (PRB) 2016 - Sari, Laila Mustika; Natalina.L, Mariani; ', Arnentis (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: the purpose of this research is to know the profile of the ability of high school students in resolving the question of Competence of the laboratory (UKL) on the activities of the Fairgrounds in biology (PRB) 2016. This research was carried out on the campus of Biology education FKIP University of Riau and junior school in Soweto who follow Fair Biology (PRB) in January to March 2017. The sample in this research are all participants Competence laboratory (UKL), which amounted to 79 people. Techniques in determination of the sample are the total sampling. Data collection instruments used in the form of a question and answer sheet student participants UKL. Parameters measured is the ability based on cognitive and psychomotor domains of students. The results showed the ability of high school students in resolving the question of Competence of the laboratory based on the cognitive domain is on the criteria is not good with average 13.8% and 10.5% in the psychomotor domain. The conclusions of the study results is a profile of the ability of high school students in resolving the question of Competence of the laboratory (UKL) on the activities of the Fairgrounds in biology (PRB) 2016 is less good.Keywords: Profile, The ability of students, Test the competence of laboratories, PRB